Update Management of Chemotherapy-Induced Neutropenia: A Narrative Literature Review - Mita Adriani; Mediarty Syahrir; Yenny Dian Andayani; Norman Djamaluddin (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
One of the most frequent and significant complicated side effects of myelosuppressive drugs is neutropenia. Neutropenia is not only associated with high morbidity but also mortality. Generally, the onset of neutropenia occurs within 3-7 days after the administration of anticancer agents. Approximately 5-30% of patients will develop febrile neutropenia. The highest incidence occurs during the first cycle of chemotherapy. This literature review aimed to describe chemotherapy-induced neutropenia and its prevention and management. Administration of granulocyte colony-stimulating factor as prophylaxis can prevent neutropenia-induced anticancer drugs. The use of granulocyte colony-stimulating factor (G-CSF) as therapeutic is contradictive, and some guidelines recommend not to use the G-CSF for therapeutic purposes. Up to 70% of mortality among these populations was associated with gram-negative sepsis, therefor empirical antibiotics, and antifungals are the keys to the management of neutropenia. In conclusion, prevention and appropriate management of neutropenia are extremely important in the treatment of patients with cancer.